Inductive Switching Noise Suppression Technique for Mixed-Signal ICs Using Standard CMOS Digital Technology - Im, Hyungjin; Kim, Ki Hyuk (Journal of Information and Communication Convergence Engineering, 14(4), 2016)
An efficient inductive switching noise suppression technique for mixed-signal integrated circuits (ICs) using standard CMOS digital technology is proposed. The proposed design technique uses a parallel RC circuit, which provides a damping path for the switching noise. The proposed design technique is used for designing a mixed-signal circuit composed of a ring oscillator, a digital output buffer, and an analog noise sensor node for 0.13-µm CMOS digital IC technology. Simulation results show a 47% reduction in the on-chip inductive switching noise coupling from the noisy digital to the analog blocks in the same substrate without an additional propagation delay. The increased power consumption due to the damping resistor is only 67% of that of the conventional source damping technique. This design can be widely used for any kind of analog and high frequency digital mixed-signal circuits in CMOS technology. KCI Citation Count: 0